A high-temperature plugging system for offshore heavy oil thermal recovery. - Yuyang Liu; Zhaoliang Li; Mao Pan (PLoS ONE)
There are many heavy oil reservoirs in offshore oilfields in China. Steam and multiple thermal fluid stimulation technologies are of increasing interest and have been applied to an increasing number of projects. During the stimulation or displacement of heavy oil reservoirs during thermal recovery, several factors, such as reservoir heterogeneity, are prone to cause channeling phenomena and affect the thermal recovery effect of steam stimulation. According to the unique requirements for the stimulation of multiple thermal fluids for offshore heavy oil, this study used transmission, blocking and relieving, heat resistance and a comprehensive evaluation of parallel sand tube experiments to conduct a screening evaluation of plugging systems for the stimulation of multiple thermal fluids, screen out a commonly used plugging agent in the current stage and propose corresponding guidance for the selection basis. The results show that foam, gel, foam gel and temperature-sensitive gel systems have a good transmission performance, whereas the oil sludge exhibits a poorer performance. The phenolic resin system exhibits great plugging properties, followed by oily sludge, temperature-sensitive gel, gel, foam gel and foam. Considering about washing resistance properties, phenolic resin system shows the best quality, followed by oily sludge and temperature-sensitive gel. The oily sludge system brings the best performance in plugging a high-permeability channel than phenolic resin gel and temperature-sensitive gel.